Energy Band Gap Modulation in Nd-Doped BiFeO3/SrRuO3 Heteroepitaxy for Visible Light Photoelectrochemical Activity - Tan, Kok Hong; Chen, Yun Wen; Van, Chien Nguyen; Wang, Hongliang; Chen, Jhih Wei; Lim, Fang Sheng; Chew, Khian Hooi; Zhan, Qian; Wu, Chung Lin; Chai, Siang Piao; Chu, Ying Hao; Chang, Wei Sea (American Chemical Society, 2019)
The ability of band offsets at multiferroic/metal and multiferroic/electrolyte interfaces in controlling charge transfer and thus altering the photoactivity performance has sparked significant attention in solar energy conversion applications. Here, we demonstrate that the band offsets of the two interfaces play the key role in determining charge transport direction in a downward self-polarized BFO film. Electrons tend to move to BFO/electrolyte interface for water reduction. Our experimental and first-principle calculations reveal that the presence of neodymium (Nd) dopants in BFO enhances the photoelectrochemical performance by reduction of the local electron-hole pair recombination sites and modulation of the band gap to improve the visible light absorption. This opens a promising route to the heterostructure design by modulating the band gap to promote efficient charge transfer. © 2018 American Chemical Society.